Asian migration and education cultures in the Anglo-sphere. Issue 14 (26th October 2017) - Watkins, Megan; Ho, Christina; Butler, Rose
ABSTRACT: Asian migration is transforming education cultures in the Anglo-sphere. This is epitomised in the mounting debates about 'tiger mothers' and 'dragon children', and competition and segregation in schools. Anxiety and aspiration within these spaces are increasingly ethnicised, with children of Asian migrants both admired and resented for their educational success. This paper presents some frameworks for understanding how Asian migration both shapes and impacts upon education outcomes, systems and cultures, focusing on Australia, the U.S., the U.K. and Canada. It challenges the cultural essentialism that prevails in academic and popular discussion of 'Asian success', arguing that educational behaviour cannot be reduced to ethnic categories, whether these are ethnic 'learning styles' (e.g. the 'Chinese learner') or 'cultural' family practices (e.g. 'Confucian parenting'). In also presenting an overview of papers in this special issue, this introduction showcases the explanatory models offered by our authors, which locate Asian migrants within broader social, historical and geo-political contexts. This includes global markets and national policies around migration and education, classed trajectories and articulations, local formations of 'ethnic capital', and transnational assemblages that produce education and mobility as means for social advancement. These are the broader contexts within which education cultures are produced.